Transcriptome analysis of salivary glands of rabies-virus-infected mice - Guo, Xin; Zhang, Maolin; Feng, Ye; Liu, Xiaomin; Wang, Chongyang; Zhang, Yannan; Wang, Zichen; Zhang, Danwei; Guo, Yidi (Frontiers in Microbiology, 2024)
Rabies is a fatal zoonotic disease posing a threat to public health. Rabies virus (RABV) is excreted in the saliva of infected animals, and is primarily transmitted through bite contact. The role of salivary glands in virus propagation is significant, but it has been less studied in RABV pathogenic mechanisms. To identify functionally important genes in the salivary glands, we employed RNA sequencing (RNA-seq) to establish and analyze mRNA expression profiles in parotid tissue infected with two RABV strains, CVS-11 and PB4. The biological functions of differentially expressed genes (DEGs) were determined through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis, revealing 3764 DEGs (678 up-regulated and 3086 downregulated) in the CVS-11 infected group and 4557 DEGs (874 up-regulated and 3683 down-regulated) in the PB4 infected group. Various biological processes are involved, including salivary secretion pathway and phosphatidylinositol 3-kinase-Akt (PI3K-Akt) signaling pathway. This study provides the first mapping of the transcriptome changes in response to RABV infection in parotid tissue for the first time, offering new insights into the study of RABV-affected salivary gland function and RABV pathogenic mechanism in parotid tissue. The salivary gland-enriched transcripts could be potential targets of interest for rabies disease control.